Digital Literature as a resource for reading comprehension development: Examples of transposition - Cuquerella Jiménez-Díaz, Ana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Digital literature can become an interesting tool to arouse interest in literary texts among students of Secondary, Baccalaureate and Vocational Training. This article analyses some characteristics of electronic literature that make it attractive to digital natives and that can be of great help in developing reading comprehension skills. Several examples are presented that constitute transpositions of canonical works. This fact favours that they can be used in the classroom as an entrance to the original works. At the end, we suggest the possibility of developing a teaching practice based on the concept of transposition and rewriting for future courses.